2021
DOI: 10.1096/fj.202100540r
|View full text |Cite
|
Sign up to set email alerts
|

High levels of eicosanoids and docosanoids in the lungs of intubated COVID‐19 patients

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
126
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(135 citation statements)
references
References 59 publications
(107 reference statements)
7
126
0
2
Order By: Relevance
“…In few cases, lipidomics studies were conducted in COVID-19 BAL samples, thus reflecting lipidomics changes in the lungs of intubated patients. The results revealed increased levels of fatty acids and inflammatory lipid mediators with both pro-inflammatory (thromboxanes, prostaglandins, leukotrienes) as well as anti-inflammatory (lipoxin A4 and the D-series resolvins) capacities [81] . In other words, the lipid mediator storm occurring in severe COVID-19 engages mechanisms operating with both pro- and anti-inflammatory lipid mediators.…”
Section: Discussionmentioning
confidence: 99%
“…In few cases, lipidomics studies were conducted in COVID-19 BAL samples, thus reflecting lipidomics changes in the lungs of intubated patients. The results revealed increased levels of fatty acids and inflammatory lipid mediators with both pro-inflammatory (thromboxanes, prostaglandins, leukotrienes) as well as anti-inflammatory (lipoxin A4 and the D-series resolvins) capacities [81] . In other words, the lipid mediator storm occurring in severe COVID-19 engages mechanisms operating with both pro- and anti-inflammatory lipid mediators.…”
Section: Discussionmentioning
confidence: 99%
“…Conti et al (2020) reported that IL-1 induces TXB2 releases in activated neutrophils and macrophages, and causes leukocyte aggregation and inflammation, which would explain the dramatic thrombi formation, platelet aggregation, and organ dysfunction in COVID-19. Moreover, results of targeted lipidomic analysis of bronchoalveolar lavages from COVID-19 patients have shown that leukotrienes, and metabolites derived from AA, EPA, and DPA were all increased ( Archambault et al, 2021 ). In the present study, the metabolic levels of DHA, resolvin D2, 5-HEPE, and 5-HETE were decreased after remdesivir treatment ( Figure 4 ), which may provide considerable mirror for understanding the mechanism of COVID-19 and antiviral drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Limited literatures have reported the metabolite changes among COVID-19 patient cohorts, such as cytosine and tryptophan–nicotinamide pathways ( Blasco et al, 2020 ), lipids ( Archambault et al, 2021 ), amino acid, and fatty acid ( Shen et al, 2020 ). However, as far as we know, no eicosanoid metabolic profiling literatures were reported pertaining to remdesivir treatment both in vitro and in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…ACE2 that is a negative regulator of the classical angiotensin-converting enzyme (ACE) in the renin-angiotensin system (RAS) was discovered to be dysregulated (decreased levels of ACE and increased levels of ACE2 in the lung cells) in patients presenting severe symptoms of COVID-19 ( 45 ). In addition, a significant increase of bioactive lipid levels modulating lung inflammation of severe COVID-19 patients, compared to healthy controls, has been reported ( 46 ). The Authors highlighted in COVID-19 patients, a predominance of cyclooxygenase metabolites, in particular significant levels of PGE2, and also increased levels of leukotrienes, compared to controls ( 46 ).…”
Section: Susceptibility To Covid-19 Infectionmentioning
confidence: 99%